Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) – Still to be Considered in the Presence of Vascular Risk Factors - Dinesh Naidu Ganesan; Thibault Coste; Narayanaswamy Venketasubramanian (Case Reports in Neurology, 2020)
Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) is a rare hereditary vasculopathy that primarily affects the brain, caused mostly by missense mutations of the NOTCH3 gene which is located on chromosome 19. Clinically, it manifests as transient ischemic attacks and strokes in individuals under the age of 60 years without vascular risk factors. We report a 46-year-old male with a 9 and 3-month history of progressive unilateral lower limb weakness and dysarthria, respectively. He had a history of diabetes mellitus but no hypertension, hyperlipidemia, or smoking history. Both parents had a stroke at the age of 65 years. Neurological examination was significant for moderate dysarthria and reduced right upper limb dexterity. Magnetic resonance imaging (MRI) of the brain revealed extensive white matter disease, lacunar infarcts, and a few microhemorrhages. Electron microscopy of his skin biopsy showed electron-dense deposits of extracellular osmiophilic granular material adjacent to smooth muscle cells. NOTCH3 gene analysis revealed a heterozygous typical mutation in exon 6. He was commenced on aspirin and atorvastatin. Over time, he became more dysarthric and demented. MRI revealed the progression of the white matter disease and a new right subcortical infarct. His aspirin was switched to clopidogrel, and donepezil was added. CADASIL should be considered among younger stroke patients with vascular risk factors, especially in the presence of widespread white matter disease. Genetic counselling may be needed after the diagnosis is made.